On the possibility of creating a hybrid meteor-burst communication system - Antipov, I.E.; Naidenova, D.R.; Shkarlet, A.I. (Radiotekhnika, 2018)
The possibility of using a meteor-burst communication for one-way transmission of short text messages is considered. The method for organizing a meteor-burst communication, which fully realizes its stealthiness and low power consumption, is proposed. According to the proposal, the meteoric radio channel is used to information transfer only from the base station to the peripheral one, and the sending of acknowledgments is via the Internet connection. The simulation results show that the proposed method can be used to transfer up to 1.5 Mbit per day.